Investigating Grammar in Autism Spectrum Disorders - Anna Gavarró (Frontiers Research Topics, 2018)
Autism Spectrum Disorder (ASD hereafter) is a neurodevelopmental condition characterized by deficits in communicative and social skills. The vast majority of research on language in ASD has focused on pragmatic difficulties, while less is known about structural aspects of language in this population. Work on syntax and phonology is not only sparse, but the heterogeneity in these grammatical domains has moreover led to conflicting reports that they are either intact or impaired. More remains to be understood about variations in grammatical profiles in ASD, as well as the relation of grammar to other cognitive abilities. The body of research gathered here increases our understanding of the grammatical strengths and weaknesses in ASD. The contributions carefully elucidate the relations between grammar and other areas of cognition, as well as unveil the similarities and differences of grammar in ASD compared to other conditions. The result is a volume that provides new ways to think about language and communication in ASD, and beyond, which should be of interest to both linguists and clinicians.